Analysis of the genetic model controlling days to flower in soybeans - Toledo, José Francisco F. de; Kiihl, Romeu Afonso de S. (Pesquisa Agropecuaria Brasileira, 2014)
Data of days to flower for six populations of soybeans (Glycine max (L.) Merrill), P1, P2, F1, F2 , RC1 and RC2, were obtained under short day conditions in a green house randomized block design experiment. P1 and P2 were represented by the line D72-7842 and the variety Santa Maria respectively. Analysis on the genetic model in control of the characteristic days to flower was performed. It was concluded that at least three genes were in control of the characteristic through additive and dominance effects. The narrow sense heritability was 84,46%.
Keywords: Glycine max (L.) Merrill